2006
DOI: 10.1103/physreva.74.043610
|View full text |Cite
|
Sign up to set email alerts
|

Dark stationary matter waves via parity-selective filtering in a Tonks-Girardeau gas

Abstract: We propose a scheme for observing dark stationary waves in a Tonks-Girardeau (TG) gas. The scheme is based on parity-selective dynamical "evaporation" of the gas via a time-dependent potential, which excites the gas from its ground state towards a desired specially-tailored many-body state. These excitations of the TG gas are analogous to linear partially coherent nondiffracting beams in optics, as evident from the mapping between the quantum dynamics of the TG gas and the propagation of incoherent light in on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Before closing, we note that dynamics of interacting Bose gases (including TG regime) may be related to incoherent light behavior in nonlinear and linear photonic structures [28,29], which motivate studies of the recently observed phenomena in optics [30] with Bose gases.…”
mentioning
confidence: 76%
“…Before closing, we note that dynamics of interacting Bose gases (including TG regime) may be related to incoherent light behavior in nonlinear and linear photonic structures [28,29], which motivate studies of the recently observed phenomena in optics [30] with Bose gases.…”
mentioning
confidence: 76%
“…This work complements the studies of nonequilibrium dynamics of interacting Bose gases which have been addressed by use of the LL model away from [18,19,20,32] and in the TG limit [35,36,43,44,45,46,47,48,49]. The phenomenological relevance of these studies is underlined by the fact that nonequilibrium dynamics is accessible experimentally [7,8].…”
Section: Introductionmentioning
confidence: 63%
“…It is hence clear that the observation of such effect in any of these dual systems would be difficult, and we turn our attention to a closely related alternative approach. Recently, a parity-selective evaporation (PSE) method has been proposed which allows to prepare in principle excited states composed exclusively of odd-parity single-particle eigenstates [21]. This is achieved by shinning a blue-detuned laser at y ∼ 0 which removes the even-parity eigenstates.…”
Section: The Tonks-girardeau and Non-interacting Fermi Gasesmentioning
confidence: 99%